1997
DOI: 10.1177/00220345970760020501
|View full text |Cite
|
Sign up to set email alerts
|

Sheathlin: Cloning, cDNA/Polypeptide Sequences, and Immunolocalization of Porcine Enamel Sheath Proteins

Abstract: Sheath proteins designate low-molecular-weight non-amelogenin enamel polypeptides and their parent protein, which concentrate in the sheath space separating rod and inter-rod enamel (Uchida et al., 1995). Two porcine sheath proteins, with apparent molecular weights of 13 and 15 kDa, are characterized by protein sequencing. The primary structures of these polypeptides match a portion of the derived amino acid sequences of clones isolated from a porcine enamel organ epithelia-specific cDNA library. Sheath protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
167
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 28 publications
0
167
0
Order By: Relevance
“…4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath. 49 It is assumed that sheathlin, its cleavage products, or both play important roles in amelogenesis, such as mediation of the contribution of ameloblasts to the mineralized matrix and the modulation of crystal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath. 49 It is assumed that sheathlin, its cleavage products, or both play important roles in amelogenesis, such as mediation of the contribution of ameloblasts to the mineralized matrix and the modulation of crystal growth.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 In the present study, we partially sequenced the amino acids of the major amyloid protein of canine APOT and compared the amino-terminal sequence with that of the enamel proteins rat ameloblastin and porcine sheathlin, which are transcribed in cells of the epithelial root sheath in normal incisor tooth germ. 16,47,48,50 We examined the immunohistochemical profile of the amyloid using antibodies to ameloblastin, sheathlin, amelogenin, and amyloid protein isolated from a canine APOT. …”
mentioning
confidence: 99%
“…During the secretory stage, ameloblasts secrete mostly amelogenin, enamelin and ameloblastin (Hu et al, 1997a;Hu et al, 1997b;Krebsbach et al, 1996;Snead et al, 1985). These proteins catalyze the extension of ribbon-like enamel crystallites comprised of the mineral calcium hydroxyapatite.…”
Section: Dental Enamel Formationmentioning
confidence: 99%
“…Since the enamelins were found to contain serum proteins (Limeback et al, 1989;Strawich and Glimcher, 1990), the more general term "nonamelogenin" is now commonly used to describe this high-molecular-weight fraction . It includes proline-rich enamelin (Fukae and Tanabe, 1987), tuftelin (Deutsch et al, 1991), and tuft proteins (Robinson et al, 1975).Three matrix proteins, corresponding to amelogenin (Hu et al, 1996), enamelin (Hu et al, 1997b), and sheathlin (also called ameloblastin or amelin) (Hu et al, 1997a), and 2 enzymes, corresponding to MMP-20 (Fukae et al, 1998) and EMSP1 (Simmer et al, 1998), have been purified and the cDNA cloned from developing porcine teeth. These proteins are all present in EMD.…”
mentioning
confidence: 99%